1992
DOI: 10.1093/geront/32.3.342
|View full text |Cite
|
Sign up to set email alerts
|

Personal and Environmental Influences on Nursing Home Satisfaction

Abstract: Data were collected from the administrator, staff, and a sample of 289 residents in 51 nursing homes in order to assess the influence of organizational factors on residents' satisfaction with the nursing home. Longevity of personnel, level of benefits, wages for nursing assistants and their perception of the charge nurse's fairness and competence as well as the degree of personalization of residents' rooms were all related to residents' satisfaction with the nursing home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 0 publications
4
59
1
Order By: Relevance
“…Similar to prior research results, only modest links were found between structural factors alone and the quality of care (Davis, 1991;Kruzich, Clinton, & Kelber, 1992). Here an effort was made to control also for residents' dependency and the mediating effect of employee stress (Hannan et al, 2001;Kruzich et al, 1992).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Similar to prior research results, only modest links were found between structural factors alone and the quality of care (Davis, 1991;Kruzich, Clinton, & Kelber, 1992). Here an effort was made to control also for residents' dependency and the mediating effect of employee stress (Hannan et al, 2001;Kruzich et al, 1992).…”
Section: Discussionsupporting
confidence: 65%
“…Here an effort was made to control also for residents' dependency and the mediating effect of employee stress (Hannan et al, 2001;Kruzich et al, 1992). In addition, the hierarchical structure of the data was acknowledged by using a multilevel methodology, an approach that has rarely been used when investigating the factors affecting the quality of institutional care (Bravo et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, understanding how care-givers perceive their role in the elders' privacy regulation may provide insights into the way elders are given more control over their privacy. In general, institutional settings often pose barriers to privacy needs of elderly individuals thus hampering their care (Gubrium, 1975;Heine, 1986;Huglund, 1985;Kayser-Jones, 1986;Kruzich, Clinton, & Kelber, 1992;Lawton & Bader, 1970;Timko & Moos, 1990;Wagnild & Manning, 1985). Knowing the extent to which institutional staff members consider the elders' privacy needs important provides some baseline information about the sensitivity care-givers have towards privacy issues.…”
mentioning
confidence: 99%
“…In constructing the Family Member Survey, several questions were taken from a 17-item satisfaction scale presented by Kruzich and colleagues (Kruzich, Clinton, & Kelber, 1992). Additional questions came from a nursing home satisfaction survey instrument developed jointly by the Scripps Gerontology…”
Section: Data Collection Overviewmentioning
confidence: 99%